2004
DOI: 10.1093/rpd/nch015
|View full text |Cite
|
Sign up to set email alerts
|

Dose-reducing strategies in combination offers substantial potential benefits to females requiring X-ray examination

Abstract: This work, using an adult anthropomorphic phantom, aimed to establish an optimised technique for ladies of child-bearing age undergoing antero-posterior (AP) pelvis and AP and lateral lumbar spine examinations. Phase one of the work involved introducing the following dose-reducing measures individually: increased kVp, increased focus-film distances, a carbon fibre cassette, a faster film/screen combination. The second phase established an optimised technique based on a combination of the parameters listed abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…A well‐defined system of exposure adaptation is required to allow accurate exposure selection for a variety of patients. Some research has gone into finding optimal exposure parameter settings for the ‘average patient’ . However, the patients that radiographers encounter will deviate from the ‘average’ and exposures will need to be adjusted accordingly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A well‐defined system of exposure adaptation is required to allow accurate exposure selection for a variety of patients. Some research has gone into finding optimal exposure parameter settings for the ‘average patient’ . However, the patients that radiographers encounter will deviate from the ‘average’ and exposures will need to be adjusted accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…Some research has gone into finding optimal exposure parameter settings for the 'average patient'. 11,12 However, the patients that radiographers encounter will deviate from the 'average' and exposures will need to be adjusted accordingly. The aim of the following review is to identify all published radiographic exposure adaptation systems which have been, or are being, used in general radiography and discuss their applicability to digital systems.…”
Section: Introductionmentioning
confidence: 99%
“…Uffmann and SchaeferProkop [4] maintain that throughout the transition from film screen to digital technology in the clinical environment many of the examination parameters such as tube current (mA), tube voltage (kVp), and filtration were translated directly from film screen exposures to computed radiography and direct digital radiography (dDR) without appropriate radiographic adjustment [4]. A review of the available optimization techniques is required so that the evidence base for optimized radiographic practice is increased and ongoing dose reductions with digital acquisition devices are achieved [5]. One such optimization technique is increasing the source to image-receptor distance (SID) for x-ray examinations within direct digital radiography.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work established that increasing the SID had the advantage of being a low-cost method of dose reduction that did not negatively impact patient comfort or image quality [8]. However, a review of the literature revealed that the research does not cover a broad range of radiographic examinations; seven studies researched anterior-posterior (AP) pelvis examinations [5,[8][9][10][11][12][13], four studies researched AP and lateral lumbar spine examinations [5,6,11,12], one study researched AP abdomen examinations [12], and one study researched AP knee examinations [7]. In addition, the level of effective dose reduction varied among authors, ranging from 8.1% for computer-simulated calculations [14] to a maximum of 44% for patient studies [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation